A meta-analytic investigation of the relationship between attentional bias and subjective craving in substance abuse - Field, Matt; Munafò, Marcus R; Franken, Ingmar H A (Psychological bulletin, 2009)
Theoretical models of addiction suggest that attentional bias for substance-related cues should be associated with self-reported craving. The authors evaluated the strength of the association by performing a meta-analysis on 68 independent data sets from which correlation coefficients between subjective craving and attentional bias indices were derived. Additional stratified analyses were conducted to identify any variables that might moderate the association between craving and attentional bias. The primary meta-analysis indicated a significant, albeit weak (r=.19), association between attentional bias and craving. Stratified analyses revealed that the association was larger for illicit drug and caffeine craving than for alcohol and tobacco craving, larger for direct measures of attention (eye movement measures and event-related potential measures) than for indirect behavioral measures of attentional bias, and larger when craving strength was high than when it was low (all ps<.05). The size of the correlation did not differ among patients in treatment and individuals who were not seeking treatment. These results suggest that attentional bias and craving are related phenomena, although the relationship is generally modest and appears to be moderated by various factors. Theoretical implications are discussed.